2015
DOI: 10.1007/s00024-015-1088-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different-Mode Fields Generated from Grounded-Wire Source Based on the 1D Model

Abstract: Abstracts-Traditional TEM study mainly focuses on the generation and application of the TE field using a loop or grounded-wire source; but in recent decades, lots of efforts have been made for implementation of the TM field and even the integration of the TE field with the TM one into anomaly detection in the subsurface. However, no applicable principles have been proposed for selecting the optimal electromagnetic field for various subsurface targets. The transient electromagnetic (TEM) fields generated from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The current mainstream electromagnetic instruments, such as V8 and GDP32, are all available for SOTEM measurement, providing favorable conditions to popularize this method. The SOTEM method has developed rapidly, with a relatively mature system of methods having been formed in the forward modeling, apparent resistivity calculation, inversion interpretation, and construction technology [40,41], and is widely and successfully applied in the areas of metal ore and coal hydrogeology [42][43][44][45].…”
Section: Magnetic Anomaly Detection Technologymentioning
confidence: 99%
“…The current mainstream electromagnetic instruments, such as V8 and GDP32, are all available for SOTEM measurement, providing favorable conditions to popularize this method. The SOTEM method has developed rapidly, with a relatively mature system of methods having been formed in the forward modeling, apparent resistivity calculation, inversion interpretation, and construction technology [40,41], and is widely and successfully applied in the areas of metal ore and coal hydrogeology [42][43][44][45].…”
Section: Magnetic Anomaly Detection Technologymentioning
confidence: 99%
“…In contrast to devices using a magnetic source, devices using an electrical source can use high power to expand the radiation range and are thus more suitable for deep exploration [24]- [26]. In addition, some researchers have investigated the fields generated by electrical and magnetic sources, and demonstrated that an electrical source can excite EM fields in both TE and TM polarization modes in the subsurface (where TE mode and TM mode are dependent upon the transverse electric waves and the transverse magnetic waves, respectively) [27]- [28]. Considering the complexity of the downhole environment and the safety of operation, crosswell EM detection methods based on electrical sources generally employ small-size electric dipole sources instead of long-wire sources [29].…”
Section: Introductionmentioning
confidence: 99%
“…The detection depth of this method can reach approximately 2,000 m. Compared with traditional LOTEM methods, the short-offset grounded-wire TEM (SOTEM) method can produce a higher signal-to-noise ratio and achieve higher detection precision at shallow depth (<2,000 m). In recent years, many research achievements have been realized with this method, and excellent deep exploration results have been obtained in the fields of mineral deposits and hydrogeological prospecting (Chen, Xue, & Khan, 2016;Xue et al, 2013Xue et al, , 2020Xue, Chen, & Cheng, 2019;Zhou, Xue, Hou, Li, & Chen, 2017;Zhou, Xue, Hou, & Lu, 2018;Zhou, Xue, & Li, 2016).…”
mentioning
confidence: 99%